Pilot Evaluation of a New Urine Progesterone Test to Confirm Ovulation in Women Using a Fertility Monitor - Bouchard, Thomas P.; Fehring, Richard J.; Schneider, Mary (Frontiers in Public Health, 2019)
Background: Progesterone rises approximately 24-36 hours after ovulation. Past studies using ultrasound-confirmed ovulation have shown that three consecutive tests with a threshold of 5 µg/mL of urine progesterone (pregnanediol-3-glucuronide, PDG), taken after the luteinizing hormone (LH) surge, confirmed ovulation with 100% specificity. Purpose: The purpose of this study was to a evaluate a new urine PDG self-test to retrospectively confirm ovulation in women who were monitoring ovulation using a hormonal fertility monitor. Methods: Thirteen women of reproductive age were recruited to test urine PDG while using their home hormonal fertility monitor. The monitor measured the rise in estrogen (estrone-3-glucuronide, E3G) and LH to estimate the fertile phase of the menstrual cycle. The women used an online menstrual cycle charting system to track E3G, LH and PDG levels for four menstrual cycles. Results: The participants (Mean age 33.6) produced 34 menstrual cycles of data (Mean length 28.4 days), 17 of which used a PDG test with a threshold of 7 µg/mL and 17 with a threshold of 5 µg/mL. In the cycles that used the 7µg/mL test strips, 59% had a positive confirmation of ovulation, and with the 5 µg/mL test strips, 82% of them had a positive confirmation of ovulation. Conclusion: The 5 µg/mL PDG test confirmed ovulation in 82% of cycles and could assist women in the evaluation of the luteal progesterone rise of their menstrual cycle.